LORD as the Foundation of Christian Marriage According to Deuteronomy 7:1-11: Addressing the Pros and Cons of Interfaith Marriage in the Indonesian Context - Manalu, Frino; Sihombing, Salomo (Jurnal Teologi Trinity, 2024)
Nowadays, the problem that occurs in the context of marriage is the occurrence of interfaith marriage. Interfaith marriage in question is a marriage between a man and a woman of different religions and each maintains the religion they adhere to. Therefore, the question of how the Christian faith actually responds to the pros and cons of interfaith marriage is important to review again. Furthermore, who or what is the basis for the continuation of marriage according to the biblical context will be traced through Deuteronomy 7:1-11. The biblical search was carried out hermeneutically-exegegetically using various related literature. This question then became the main problem to be studied in this paper. The findings from the biblical search of Deuteronomy 7:1-11 show that LORD is the basis and key to the continuation of an ideal marriage in order to respond to the pros and cons of interfaith marriage.